Hemocyte quantitative changes in Anticarsia gemmatalis (Lepidoptera: Noctuidae) larvae infected by AgMNPV - Fábio Goulart de Andrade; Maria Cláudia Cordeiro de Negreiro; Sheila Michele Levy; Inês Cristina de Batista Fonseca; Flávio Moscardi; Ângela Maria Ferreira Falleiros (Brazilian Archives of Biology and Technology, 2010)
The initial effects of the infection by AgMNPV in the total and differential counts of the hemocytes in Anticarsia gemmatalis (Lepidoptera: Noctuidae) larvae were studied. The total number of the hemocytes did not decrease in infected larvae, as it occurred in non infected larvae. In infected larvae, the hemocyte types showed the following frequencies: plasmatocytes - 47.8%, esferulocytes - 25.9%, granulocytes - 15.8%, oenocytoids - 7.2%, prohemocytes - 2.8%, vermicytes - 0,5%. Only the percentage of the granulocytes was different among infected and non infected larvae, indicating that these cells responded quickly to the initial viral infection. These results showed the effective role of the hemocytes in the response of the A. gemmatalis to the infection by AgMNPV. The comprehension of the immunological mechanisms of this insect is an important tool to understand its biological control. Os efeitos iniciais da infecção por AgMNPV nas contagens total e diferencial dos hemócitos em Anticarsia gemmatalis (Lepidoptera: Noctuidae) foram estudados. O número total de hemócitos não diminuiu nas larvas infectadas, como ocorreu nas larvas não infectadas. Nas larvas infectadas, os tipos de hemócitos apresentaram as seguintes freqüências: plasmatócitos - 47,8%, esferulócitos - 25,9%, granulócitos - 15,8%, oenocitóides - 7,2%, prohemócitos - 2,8%, vermiformes - 0,5%. Apenas a porcentagem de granulócitos foi diferente entre larvas infectadas e não infectadas, indicando que estas células responderam rapidamente à infecção viral inicial. Estes resultados mostraram o papel efetivo que dos hemócitos na resposta de A. gemmatalis à infecção por AgMNPV. A compreensão dos mecanismos imunológicos deste inseto é uma ferramenta importante para compreender seu controle biológico.